Program Mutu Multimedia dalam Pendidikan Digital Era 5.0 di Prodi KPI (Komunikasi dan Penyiaran Islam) UIMSYA Banyuwangi - Akbar, M Ilham Faizin; Maksum, Ali; Firmansyah, Derby (TSAQOFAH, 2025)
This study aims to analyze the implementation of a multimedia quality program to support the learning process in the Digital Education 5.0 era within the Islamic Communication and Broadcasting Study Program (KPI) at Universitas KH. Mukhtar Syafaat (UIMSYA) Banyuwangi. This era demands a synergy between technology and humanistic values in higher education systems. A qualitative descriptive approach was employed, with data collected through in-depth interviews, participatory observation, and documentation. The findings indicate that the KPI Study Program at UIMSYA has implemented the multimedia quality program by utilizing a Learning Management System (LMS), integrating audiovisual media into courses, providing digital content production training for lecturers and students, and collaborating with local media for broadcasting practice. This implementation supports the achievement of Graduate Learning Outcomes (CPL), enhances students’ digital competencies, and strengthens both online and offline learning interactions. Challenges faced include limited infrastructure, human resource capacity, and digital literacy gaps among students. Nonetheless, program evaluation is conducted regularly with strengthened interdisciplinary collaboration. The study recommends reinforcing a multimedia-based curriculum, increasing investment in educational technology, and developing local content as adaptive strategies to address the challenges of the Digital Education 5.0 era.